Surgical Treatment of Extracranial Arteriovenous Malformations after Multiple Embolizations. Issue 2 (February 2015) - Goldenberg, Dov C.; Hiraki, Patricia Y.; Caldas, Jose Guilherme; Puglia, Paulo; Marques, Tatiana M.; Gemperli, Rolf
<x xml:space="preserve">Abstract</x> Background: Surgical resection after embolization is the most accepted approach to treating arteriovenous malformations. The authors analyzed the outcome of surgically treated patients and how surgical resection was influenced by multiple embolizations. Methods: Thirty-one patients were included from January of 2000 to December of 2012. The mean patient age was 24.9 years. Anatomical involvement, definition of limits, functional impairment, number of embolizations, type of resection, reconstruction method, blood transfusion, and hospital stay were evaluated. Morbidity, mortality, and regrowth rates and need for additional procedures were evaluated. Results: Lesions were preferentially located at the orbits, cheeks, and lips. The number of embolizations per patient increased with lesion complexity. In 22 cases, total excision was accomplished, and in nine, subtotal resections were performed to favor function. After multiple embolizations, better lesion identification was observed. Primary closure was performed in 20 cases, local flaps were performed in seven cases, axial flaps were performed in two patients, and free flaps were performed in two cases. There were no deaths. Regrowth rates were influenced by limits between arteriovenous malformations and surrounding tissues (15.8 percent of cases with precise limits versus 58.3 percent of lesions with imprecise limits; p = 0.021) and by type of resection (18.2 percent of cases after total resection versus 66.7 percent after subtotal resections; p = 0.015). Conclusions: Multiple therapeutic embolizations seem to increase safety in the treatment of arteriovenous vascular malformations and suggest an additional positive effect besides bleeding control. Preoperative definition of limits and establishment of conditions for total resection are critical to determine management and risk of regrowth. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.